Effect of Diglyme on the performance, emission and combustion characteristics of diesel engine fuelled with methyl ester of rubber seed oil. Issue 1 (31st December 2022) - Jeyakumar, Nagarajan; Bose, N.
Abstract : The present study analyses the effect of oxygenated additive Diglyme on engine performance, emission and combustion characteristics of a compression ignition engine fuelled with Rubber Seed Oil Methyl Ester blend. The biodiesel prepared through transesterification process has properties as per ASTM standards. Results show that the addition of Diglyme improves the Brake Thermal Efficiency and reduces Brake Specific Fuel Consumption. The oxygenated additive Diglyme was found to be efficient in the reduction of CO, HC and smoke emissions with the penalty of NOx . The % increase in BTE and NOx found to be 4.01 and 1.38, respectively for 15% Diglyme blend of biodiesel. The % decrease in BSFC, CO, HC and smoke emissions was observed to be 14.3, 29.7, 56.9 and 9.2, respectively. Combustion parameters, such as cylinder pressure, Heat Release Rate, Mass Fraction Burnt, Cumulative Heat Release Rate and mean gas temperature, have been analysed for the fuel blends.